2000
DOI: 10.1161/01.cir.101.23.2742
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Myocardial Ischemia/Reperfusion Injury by Superinduction of Inducible Nitric Oxide Synthase

Abstract: Background-Nitric oxide (NO) has been implicated as a mediator in myocardial ischemia/reperfusion (I/R) injury, but its functional properties have been conflicting. We investigated whether NO has a protective role against I/R injury. Methods and Results-Using endothelial NO synthase knockout (eNOS KO) mice, inducible NOS KO mice, the NO donor S-nitroso-N-acetylpenicillamine (SNAP), and the NOS inhibitor N-iminoethyl-L-ornithine (L-NIO), we performed studies of isolated perfused hearts subjected to 30 minutes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
110
1
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(118 citation statements)
references
References 45 publications
6
110
1
1
Order By: Relevance
“…Recently, many investigators have documented the role of eNOS 10,37 or iNOS 18,38,39 in the cardioprotective effect of IP. Our data suggest that in the case of I-R injury after IP, activated eNOS produced from recruited EPCs plays an essential role in cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many investigators have documented the role of eNOS 10,37 or iNOS 18,38,39 in the cardioprotective effect of IP. Our data suggest that in the case of I-R injury after IP, activated eNOS produced from recruited EPCs plays an essential role in cardioprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented a favorable role of iNOS in IP. 18,38,39 In particular, Wang et al 40 reported that IP upregulated iNOS in cardiomyocytes and played a protective role against myocardial damage. These authors showed iNOS mRNA expression in ischemic myocardium followed IP, and diffuse iNOS signals were detected with in situ hybridization and immunohistochemistry in the cytoplasmic space of cardiomyocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research, the role of NO in ischemia and reperfusion injury remains controversial and is yet to be defined (10,11). However, several reports demonstrated that NO functions as a protective agent during reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, myocardial superinduction of inducible NOS has been described in eNOS-knockout mice but not in WT mice after severe myocardial ischemia as an adaptive response mediating protective effects. 50 Furthermore, recent studies suggest a protective role of neuronal NOS in the myocardium. Thus, the potential compensatory mechanisms in eNOS Ϫ/Ϫ mice with severe LV dysfunction (ie, mediated by inducible or neuronal NOS or other vasodilator systems) need to be addressed in future studies.…”
Section: Landmesser Et Al Statin Therapy and Enos After MImentioning
confidence: 99%